2019
DOI: 10.20998/2074-272x.2019.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Methods for Monitoring of Existing Energy Objects Grounding Devices State at the Present Stage

Abstract: Purpose. The purpose of the work is to analyze the modern methods of control and determine the most effective ones for monitoring the state of grounding of existing energy objects in operation. Methodology. The analysis of the methods was carried on the basis of comparison the experimental and calculation methods for determining the rated parameters of the grounding of existing energy objects. Results. Significant imperfections of measurements of the rated parameters of the grounding with different methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…showed that during SC in the power system, exceeding the permissible value of touch voltage at power facilities is fixed at more than 75 % of substations with voltage class of 110-750 kV. The most widespread in the world practice of monitoring the safe operation of electrical installations and during experimental measurement of touch voltage at power facilities is a method based on the use of the «low current method» followed by reduction of the measured touch voltage in direct proportion to the ratio of the actual SC current to the measuring current at the facility [31,32]. A method based on the application of direct SC current for these purposes is extremely dangerous both for electrical equipment and for technical personnel serving it.…”
Section: A Generator Ti-cs116 (Ncs09)mentioning
confidence: 99%
See 1 more Smart Citation
“…showed that during SC in the power system, exceeding the permissible value of touch voltage at power facilities is fixed at more than 75 % of substations with voltage class of 110-750 kV. The most widespread in the world practice of monitoring the safe operation of electrical installations and during experimental measurement of touch voltage at power facilities is a method based on the use of the «low current method» followed by reduction of the measured touch voltage in direct proportion to the ratio of the actual SC current to the measuring current at the facility [31,32]. A method based on the application of direct SC current for these purposes is extremely dangerous both for electrical equipment and for technical personnel serving it.…”
Section: A Generator Ti-cs116 (Ncs09)mentioning
confidence: 99%
“…The voltmeter is shunted by a resistor with resistance R В , which should be equal to the resistance of the human body (as a rule, it is taken equal to about 1000 ). The horizontal distance from the place of contact of the human feet to the plate to the metal structure of the object is assumed to be from 0.8 m to 1 m [32]. The current electrode C (see Fig.…”
Section: A Generator Ti-cs116 (Ncs09)mentioning
confidence: 99%
“…The work according to item 3 of the experimental stage is performed by the method of vertical electric sounding (using the Wenner or Schlumberger arrangement), and according to item 4 -by the ammetervoltmeter method (by potential drop, four-point or «62% method») [10].…”
Section: Analysis Of Publications Within the Framework Of European Imentioning
confidence: 99%
“…Studying the writings (Gracheva and Naumov, 2019;Koliushko and Rudenko, 2019;Kosyakov et al, 2019;Vinogradov et al, 2020), we discovered that there is no mathematical model to describe the process of measuring the resistance of the protective device of the 110 kV OHL supports. This is a gap in the research that aims to increase the efficiency of resistance measuring of those protective devices.…”
Section: Introductionmentioning
confidence: 99%